Analysis of Curriculum 13 and Class XI Pancasila and Civic Education Textbook at Al-Azhar Mandiri High School Palu - Shofia Nurun Alanur; Jamaludin Jamaludin; Sukmawati Sukmawati; Siti Rukmana; Nurul Asrina; Ishak Ishak; Putri Apriani; Fitriani Fitriani; Lisa Selviana; Nuraftitah Nuraftitah; Elma Tiana; Asyer Emarvino Kaitu; Andi Rahmatullah (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2023)
This study aims to describe the Application of PPKn Curriculum and Textbooks in Al-Azhar Mandiri High School Palu, especially in grade XI. The research uses qualitative methods and data collection techniques, namely by observation. The results of the research (1) The curriculum applied at SMA Al-Azhar Mandiri Palu is the 2013 curriculum, as for the curriculum that has been applied at SMA Al-Azhar Mandiri Palu, namely, the KBK Curriculum, the KTSP Curriculum, and the 2013 Curriculum which is valid to date. However, in 2022 it began to adopt several things from the Independent Curriculum, for example, regarding formative assessments, defensive learning (2) The PPKn textbooks used in this school adjust to the applicable curriculum, and see the suitability of the material from the student and teacher handbook PPKn books with the achievement of Competency Standards and Basic Competencies of students and students.